Nanosized SnO2-CoS constructed porous cubeas advanced lithium-ion batteries anode. Issue 5 (1st April 2018) - Zhang, Xinqun; Sun, Yanfang; Li, Huiping; Guo, Jinxue; Zhang, Xiao
Abstract: Porous frameworks with geometry nanostructures have attracted increasing research interest due to their specific architectures which offer structural advantages for energy conversion and storage. Here, we firstly report the synthesis of porous cubes constructed by hybrid SnO2 -CoS nanoparticles using cubic CoSn(OH)6 precursor as template. The porous nanostructures, nanosized subunits, as well as the cubic geometry feature offer abundant pores and channels for electrolyte diffusion, ensure large contact surface area between electrolytes and active materials, shorten transport distance of lithium ion, and supply voids to buffer the huge volume variation, making it an ideal candidate for reversible lithium storage. When used as anode material for lithium-ion batteries (LIBs), the developed sample exhibits outstanding electrochemical properties of large reversible capacity, high rate capability, and stable durability (750 mAh g −1 at 100 mA g −1 after 100 cycles).